Perfil comportamental e desempenho acadêmico em Ciências Contábeis: uma análise à luz da teoria DISC - Paula, Chiara Raiol (2023)
This study aims to analyze the relationship between behavioral profile, based on the DISC theory, and academic performance in accounting science students. The DISC theory classifies behavioral profiles into four main categories: Dominance, Influence, Stability, and Compliance. The research included 352 undergraduate accounting science students from the Federal University of Rio Grande do Norte (UFRN), selected through a non-probabilistic accidental sample. Johnson's (2018) psychometric test was used to identify the DISC behavioral profiles of the participants. Data analysis was performed using descriptive statistics and multiple linear regression, considering the 4 types of DISC behavioral profiles and sex, age group, educational center, and academic year as control variables. A positive association was observed between the Stability and Compliance profiles and the students' academic performance. However, excessive adherence to the characteristics of Stability can be detrimental, indicating resistance to new situations, teaching methods, and difficulties in exercising critical judgment, suggesting the need for a balance between the different profiles for effective academic performance. Furthermore, the results indicate a significant influence of demographic factors, with female students and older students generally showing superior performance, which may be indicated by the type of compliance profile presented throughout the course. These findings suggest that understanding DISC behavioral profiles can be a valuable tool in understanding and improving teaching and learning strategies in accounting sciences. It is important to highlight that the study is limited to the context of the UFRN, potentially affecting the generalization of the results, the absence of institutional, teaching, and socioeconomic variables, and the sensitivity of the DISC test to cultural issues. Therefore, future research is suggested to seek a more representative sample and consider different academic contexts to validate and expand the findings of this study. Additionally, exploring how DISC profile-based interventions can be practically implemented in the educational environment.